Distribution of Positron Annihilation Lifetime Components - Ahmed Abdul-Razzaq Selman; Muna Ahmed Saeed (مجلة بغداد للعلوم, 2008)
The intensities of the positron annihilation lifetime components are shown to be related to the free volume model, and the theoretical value of the ratio between the singlet to the triplet state intensities, described by the ratio η, is shown to follow an empirical model.  An application of the model on some experimental data shows that the calculated value of the ratio η approaches the theoretical value, which is 1/3.